The Association between D-dimer Concentration and Laboratory Parameters for Plasma Leakage in Dengue Infection - Suwarto, Suhendro; Diahtantri, Riyanti Astrid; Hudiya, Elian (UI Scholars Hub, 2018)
Introduction. Plasma leakage and activation of the coagulation system are the pathological hallmark of dengue hemorrhagic fever (DHF) that causes an increase in D-dimer concentration due to the degradation of fibrin clots. This study was conducted to determine the association between of D-dimer and laboratory parameters of plasma leakage, namely: thrombocytopenia, hypoalbuminemia, hemoconcentration and concentration serum glutamic oxaloacetic transaminase (SGOT) in dengue infected patients. Methods. A retrospective study was conducted at private hospitals in Jakarta, from December 2016 to March 2018. Patients >14 years with dengue infection and positive NS-1 were included in this study, and were classified into dengue fever (DF) group or DHF group. The Mann Whitney test was used for non-parametric variables and the Spearman test was used for the correlation for non-normally distributed numeric variables. Results. Seventy-three dengue infected patients included in this study consists of 29 (39.7%) female and 44 (60.3%) male. Total of 43 (58.9%) were classified as DD group, 30 (41.1%) were classified as DHF group. The D-dimer concentration of the DHF group in the fever phase was higher compared to the DD group (p = 0.004). There was a weak correlation in the fever phase between D-dimer concentration and the degree of thrombocytopenia (r = 0.35; p = 0.003) and weak inverse correlation in the fever phase between D-dimer concentration and albumin concentration (r = -0.34; p = 0.049). We found a weak correlation in the critical phase between D-dimer concentration and the degree of thrombocytopenia (r = 0.39; p = 0.034) and the moderate inverse correlation in the critical phase between the D-dimer concentration and albumin concentration (r = -0.43; p = 0.032). Conclusions. D-dimer concentrations in DHF patients in the fever phase are higher compare to DD patients. D-dimer concentration correlates with the degree of thrombocytopenia and hypoalbuminemia.